Contextualizing solove’s taxonomy of privacy in the data life cycle - Sant’ana, Ricardo César Gonçalves [UNESP] (2024)
In the Data Life Cycle privacy is a factor that can permeate all phases. However, understanding the concept of privacy can be a complex task. Daniel Solove (2006) describes the so-called Taxonomy of Privacy, which addresses the complexity of privacy breaches. The aim of this study is to relate the scenario proposed in a fictional narrative to the context of privacy breaches. Through a process of segmentation, the episode «Joan is awful» from the series Black Mirror, was divided into 33 sequences to identify the circumstances in which the privacy of the main character of the episode (Joan, by Annie Murphy) was breached, in terms of the Taxonomy of Privacy, bringing greater concreteness to the issue of privacy. Out of the 16 subgroups proposed in the Taxonomy of Privacy, it was observed that the breach of Joan’s privacy occurred in 5 distinct subgroups throughout the episode.